Seasonal forecasts of the 20th century - Weisheimer, A; Befort, DJ; MacLeod, D; Palmer, T; O’Reilly, C; Strømmen, K (American Meteorological Society, 2020)
New seasonal retrospective forecasts for 1901-2010 show that skill for predicting ENSO, NAO and PNA is reduced during mid-century periods compared to earlier and more recent high-skill decades.